Efficacy of the need ratio for prediction of respiratory condition during sleep following pharygeal flap operation - HARA, Hisanaga; TACHIMURA, Takashi; WADA, Takeshi; SATOH, Koichi (Japanese Journal of Oral and Maxillofacial Surgery, 1996)
Pharyngeal flap surgery may be used to correct hypernasality following primary palatal closure with a pharyngeal flap to create airway resistance. Obstructive sleep apnea has been reported to be one of the serious complications after operation. However, there has been no report made on how to predict postoperative changes in sleep condition. This article attempts to estimate the possibility of predicting postoperative changes in sleep condition with the need ratio (NR), based on the velopharyngeal distance divided by the velum length, which is obtained from lateral cephalograms taken preoperatively. Fifteen patients who underwent unified velopharyngoplasty to correct velopharyngeal incompetence were selected as subjects. Oxygen saturation during sleep was recorded daily after operation in all subjects. The lowest value of mean SpO2(Lo-SpO2) was considered to be representative of postoperative sleep condition. Statistical analysis showed a significant correlation between Lo-SpO2 and NR. It was suggested that NR could be an indicator for postoperative sleep changes.